Implementasi Algoritma A-Star pada Sistem Pencarian Jalur Terdekat Objek Wisata Di Aceh Utara - Amrullah, Novia Hasdyna, Zulfikar (Jurnal Elektronika dan Teknologi Informasi, 2023)
The A* (Astar) algorithm is an algorithm that is included in the category of informed search methods. This algorithm is very good as a solution to the path finding process. This algorithm looks for the shortest route distance that will be taken from a starting point to the North Aceh tourist attraction. The search technique used in this simulation is the A* algorithm with a heuristic function. The main aim of this research is to study how the A* algorithm works in finding the fastest distance, which simulates conditions when someone is looking for a route in a traffic jam. This simulation provides a more realistic picture of the behavior of the A* algorithm in finding the shortest route distance to North Aceh Tourist Attractions.